2010
DOI: 10.1038/aja.2010.41
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body heat exposure induces membrane changes in spermatozoa from the cauda epididymidis of laboratory mice

Abstract: This study was carried out to determine if exposure to hot environmental temperatures had a direct, detrimental effect on sperm quality. For this the effect of whole-body heat exposure on epididymal spermatozoa of laboratory mice was investigated. C57BL/6 mice (n = 7) were housed in a microclimate chamber at 37ºC-38ºC for 8 h per day for three consecutive days, while control mice (n = 7) were kept at 23ºC-24ºC. Cauda epididymal spermatozoa were obtained 16 h after the last heat treatment. The results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 37 publications
1
15
0
3
Order By: Relevance
“…It is clear that psychological and physiological effects of stress can lead to endocrine and functional disorders in the testis (Pook, Tuschen‐Caffier, & Krause, ). Moreover, previous reports have demonstrated that HS exposure induces sperm motility reduction and sperm chromatin abnormality and apoptosis increases (Sailer, Sarkar, Bjordahl, Jost, & Evenson, ; Wechalekar et al, ). Therefore, HS affects reproductive performance and can result in human and animal infertility (Setchell, ; Venkatachalam & Ramanathan, ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It is clear that psychological and physiological effects of stress can lead to endocrine and functional disorders in the testis (Pook, Tuschen‐Caffier, & Krause, ). Moreover, previous reports have demonstrated that HS exposure induces sperm motility reduction and sperm chromatin abnormality and apoptosis increases (Sailer, Sarkar, Bjordahl, Jost, & Evenson, ; Wechalekar et al, ). Therefore, HS affects reproductive performance and can result in human and animal infertility (Setchell, ; Venkatachalam & Ramanathan, ).…”
Section: Discussionmentioning
confidence: 92%
“…It has been shown that experimental scrotal hyperthermia leads to suppressing spermatogenesis in several studies in rats (Guo et al, ), mice (Li et al, ), monkeys (Zhang et al, ) and humans (Rao et al, ). Moreover, it is well documented that intratesticular temperature increase has adverse effects on spermatogenesis; thus, extrinsic HS in the scrotum may have been associated with sperm abnormality and spermatozoa apoptosis (Jung & Schuppe, ; Wechalekar et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Sperm motility can be restored by increasing the level of ATP in sperm suspending media (Gong et al, 2017). Increased environmental (Gong et al, 2017) or body temperature (Wechalekar et al, 2010) affect the mitochondrial activity by inducing oxidative stress (Zhao et al, 2006). Recently, it has been observed that oxidative phosphorylation level, ATP contents and sperm motility events are linked to each other (Guo et al, 2017) and low mitochondrial activity due to HS affect the whole pathway of sperm motility (Gong et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…I am currently cosupervisor of three Ph.D. students, one in Anatomical Sciences looking at the effects of heat on epididymal spermatozoa [100] and two in the Department of Obstetrics and Gynecology working on the effects of obesity on reproduction in males [101,102]. I continue to referee papers for a range of journals and try to attend relevant scientific meetings whenever possible.…”
Section: Setchellmentioning
confidence: 98%